Asian International Students' Perceptions of their University Experience - Cody J. Perry; Jennifer Weatherford; David Lausch (ÜNİVERSİTEPARK Limited, 2016)
Asian students make up the largest proportion of international students who study in the United States. Seeking a degree in higher education can be challenging for any student, but Asian students often encounter more obstacles to completion than many other international and domestic students. Culture, family and health concerns, and safety are some of the largest concerns that this study found among Asian students in the US. The study found that East-Asian international students had more issues than students from other parts of Asia and difficulty with the English language was of major importance to respondents. In addition, safety is an issue that Asian students were concerned with while studying in the US. The study was exploratory in nature and informs the field on future avenues of research.